Silence as Complicity: Elements of a Corporate Duty to Speak Out Against the Violation of Human Rights - Wettstein, Florian (Business ethics quarterly, 2012)
Increasingly, global businesses are confronted with the question of complicity in human rights violations committed by abusive host governments. This contribution specifically looks at silent complicity and the way it challenges conventional interpretations of corporate responsibility. Silent complicity implies that corporations have moral obligations that reach beyond the negative realm of doing no harm. Essentially, it implies that corporations have a moral responsibility to help protect human rights by putting pressure on perpetrating host governments involved in human rights abuses. This is a controversial claim, which this contribution proposes to analyze with a view to understanding and determining the underlying conditions that need to be met in order for moral agents to be said to have such responsibilities in the category of the duty to protect human rights.